PEMAHAMAN ORGANISASI KEPEMUDAAN DI DESA BATU MERAH AMBON TERHADAP TAFSIR JIHAD UPAYA SOLUTIF MENCEGAH PEMAHAMAN RADIKALISME - Roswati Nurdin; Samsir Salam (TAHKIM, 2018)
Basically jihad is all the work done with sincerity to achieve a purpose. Although the meaning of jihad is so simple, but not so in understanding. Misunderstanding the purpose interpret jihad is contained in the Koran can lead to a radical action that leads to terrorism, so that the appropriate meaning of jihad need to be explored by the method of strengthening the understanding. The data collection was done through structured interviews and documentation methods forum group discussion (FGD). The results showed that the understanding of youth organizations in the village of Batu Merah Ambon the Islamic Students Association (HMI), the Muhammadiyah Students Association (IMM), the Indonesian Islamic Students Movement (PMII) and the Indonesian National Youth Committee) of the meaning of jihad is also varied. However, such diversity is still within the scope of understanding of the meaning of jihad, according to some scholars.